Environmental shocks and sustainability in a basic economy-environment model. (1st January 2013) - Privileggi, Fabio; Marsiglio, Simone
We study a stochastic, discrete-time, economy-environment integrated model, where human activity affects the evolution of pollution over time. We assume that exogenous i.i.d. environmental shocks determine the rate of pollution transfer. We show that the pollution to capital ratio dynamics can be read as an iterated function system converging to an invariant distribution supported on a (asymmetric) Cantor set, and that human intervention aiming at offsetting the environmental impact of economic activities is needed to ensure sustainability.